Enhanced Capacity and Easily Separable Adsorbent of Dithizone-immobilized Magnetite Zeolite for Pb(II) Adsorption - Susiana, Carissa Ayu; Rusdiarso, Bambang; Mudasir, Mudasir (Universitas Gadjah Mada, 2024)
In this study, magnetic natural zeolite (ZTM) was prepared using the coprecipitation method and dithizone was then immobilized on its surface in less toxic medium of alkaline to yield dithizone-immobilized magnetic zeolite (ZTM-Dtz). The synthesized ZTM-Dtz was characterized by FTIR and XRD, indicating that dithizone was successfully immobilized on the surface of ZTM. Vibrating sample magnetometer measurements showed superparamagnetic properties of either ZTM or ZTM-Dtz with magnetization values of 7.35 and 11.49 emu g−1, respectively. The adsorption kinetics of Pb(II) on both adsorbents followed a pseudo-second-order and their adsorption isotherms were properly described by the Langmuir model. The adsorption capacity of ZTM and ZTM-Dtz were 6.94 and 38.46 mg g−1, respectively, suggesting that dithizone immobilization enhanced the adsorbent capacity more than 5 times. The interaction mechanism between Pb(II) metal ion and ZTM was dominated by ion exchange, whereas that of ZTM-Dtz was mostly hydrogen bonds and complexation. The synthesized material is promising to be developed for the adsorption of heavy metal ions such as Pb(II) because it provides a high adsorption capacity and the adsorbents can be easily separated magnetically after application.